Biomechanical impact of enoxaparin sodium-chitosan-PMMA bone cement in hip arthroplasty: a preliminary finite element analysis - Chen, Jianchao; Ma, Xinzhe; Li, Zhiyong; Fan, Weiye; Ma, Lijie (Frontiers in Surgery, 2025)
ObjectiveTo determine the material parameters of PMMA and ES-CS-PMMA, and compare the stress distribution differences in hip arthroplasty postoperatively using finite element analysis.MethodsThe Young's modulus and Poisson's ratio of PMMA and ES-CS-PMMA were calculated by measuring the propagation speed of ultrasound waves through the bone cements. Using CT images of a healthy adult male, a three-dimensional model of the natural femur and two postoperative 3D models (with PMMA and ES-CS-PMMA as adhesives) were established. Simulating slow walking motion, stress distribution differences in the cement sheath and femur were observed between the two postoperative models.ResultsThe Young's modulus of PMMA was 4,127 MPa with a Poisson's ratio of 0.25; ES-CS-PMMA exhibited an Young's modulus of 4,331 MPa and a Poisson's ratio of 0.28. In the two postoperative models, no significant differences were observed in stress distribution within the cement sheath or femur after prosthesis implantation. Compared to the natural femur, both PMMA and ES-CS-PMMA reduced cortical stress postoperatively, transferring stress to the femoral stem. In the distal region of the prosthesis, mean stress was significantly reduced post-implantation. In the midsection of the prosthesis, the implanted prosthesis bore higher peak stress than the natural femur.ConclusionsThis study measured the material parameters of PMMA and ES-CS-PMMA. Compared to PMMA, using ES-CS-PMMA as an adhesive in hip arthroplasty did not alter the stress distribution of the cement sheath or femur post-implantation.